The normative chaos of the global arena. The COVID-19 pandemic as a litmus test for the health emergency management and global health systems - Piroddi, Corrado (Journal of global ethics, 2025)
The paper highlights how the normative and institutional anarchy of the global arena, where opposite practical and political logic and conflicting values are often at play, prevents any significant realization of principles of health justice or substantive conception of health and well-being. This point is illustrated by focusing on problems related to the COVID-19 global response: the characterization of individual and population health and differences and asymmetries in national healthcare systems. The paper suggests that any bioethical framework that aspires to evaluate global health questions cannot avoid focusing on the problem of social and political domination: Both the mitigation of health iniquities and global acknowledgment of a minimal conception of good health and well-being might benefit from the fulfillment of another crucial task: minimizing and mitigating asymmetries of power and situations of dependency among different countries, international institutions and economic stakeholders.